2008
DOI: 10.1021/ja806962e
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Tuning of Green Fluorescent Protein Chromophore Emission by Alkyl Substituent-Mediated Crystal Packing

Abstract: O-Alkyl synthetic analogues of the green fluorescent protein chromophore are nonfluorescent in solution but demonstrate a bright emission in the crystalline state. Three-dimensional steady-state and time-resolved emission spectroscopies in the solid state, as well as single-crystal X-ray diffraction, reveal the nature of complex emission in the crystals. A hypsochromic emission shift with an increase of the alkyl size is determined by the monomer-aggregate emission ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
98
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 76 publications
8
98
0
1
Order By: Relevance
“…[6][7][8] Although GFP was discovered more than 20 years ago, the photophysics of p-HBI and of its mutants is still intensively investigated mainly because of the spectacular decrease of its fluorescence quantum yield, Φ fl , and lifetime, τ, taking place when going from the protein (Φ fl ) 0.79, 9 τ ) 3.3 ns) 8,10 to liquid solutions (Φ fl < 10 -3 , 11 τ < 1 ps). [12][13][14] In this respect, the photophysical properties of the synthetic dimethyl derivative of the GFP chromophore (p-HBDI) 13,[15][16][17][18][19][20][21][22][23][24][25][26] and other related model systems 24,25,[27][28][29][30][31][32] have been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Although GFP was discovered more than 20 years ago, the photophysics of p-HBI and of its mutants is still intensively investigated mainly because of the spectacular decrease of its fluorescence quantum yield, Φ fl , and lifetime, τ, taking place when going from the protein (Φ fl ) 0.79, 9 τ ) 3.3 ns) 8,10 to liquid solutions (Φ fl < 10 -3 , 11 τ < 1 ps). [12][13][14] In this respect, the photophysical properties of the synthetic dimethyl derivative of the GFP chromophore (p-HBDI) 13,[15][16][17][18][19][20][21][22][23][24][25][26] and other related model systems 24,25,[27][28][29][30][31][32] have been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…24,25,[27][28][29][30][31][32] For example, Solntsev et al 32 have compared the ultrafast excitedstate dynamics of p-HBDI and m-HBDI in aqueous solutions and have found that the deactivation by large amplitude motion was slower with the m-HBDI, due possibly to a higher barrier for Z/E isomerization.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of the isomerization by aggregate formation may be responsible for the AIE effect of its aggregates, as the photoinduced conformation change has been considered to be a root cause of quenching fluorescence of unrestrained fluorogens in biological systems, such as blue fluorescent anti-bodies 43 and green fluorescence proteins (GFP). 44,45 It has been already hypothesized that trapping of the stilbene and hydroxybenzylideneimidazolinone chromophores by the ligand-binding pockets of the antibodies and b-barrel of GFP respectively, have suppressed the E/Z isomerization and revived the fluorescence processes. [43][44][45] This suggests that restriction in the EZI process upon aggregation could be the cause of AIE/CIE behavior.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 It has been already hypothesized that trapping of the stilbene and hydroxybenzylideneimidazolinone chromophores by the ligand-binding pockets of the antibodies and b-barrel of GFP respectively, have suppressed the E/Z isomerization and revived the fluorescence processes. [43][44][45] This suggests that restriction in the EZI process upon aggregation could be the cause of AIE/CIE behavior. On the other hand, according to the RIR mechanism, in the solution phase, the dynamic intramolecular rotation (IMR) of its multiple phenyl rotors against its ethylene stator serves as a relaxation channel for the decay of the excited state.…”
Section: Introductionmentioning
confidence: 99%
“…[43,44] Tw oe mission centers with distinct decay kinetic were assigned to monomer and excimer emission of the chromophore,inl ine with the crystallographic and computational results.T he p-p stacking in the crystal structure of 4 ( Figure 2C)f acilitates the formation of excimer,a nd this hypothesis is in line with the quantum chemical calculations on ad imer of 4 ( Figure 4E,F). Each of the DASi sc haracterized with as ingle decaying component with lifetimes of 160 ps and 1.9 ns,c orrespondingly.T he fit necessitated inclusion of an intermediate DAS with am aximum at 490 nm and al ifetime of 390 ps (further details are available from the Supporting Information).…”
mentioning
confidence: 99%